The Language of Hospitality: Linguistic Strategies for Improving Tourist Satisfaction - Nahlah Nafea Khorsheed; Houshyar Abdulrahman Saleh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The present study aims to examine the complex dynamics of linguistic techniques employed in the hospitality business and their influence on the level of satisfaction experienced by tourists. By employing quantitative analysis, this study investigates the associations between several linguistic and cultural variables and the level of satisfaction among tourists. The aim is to provide insights into effective approaches to improve the overall experience of visitors Baghdad and other south cities. The data is collected on many criteria to measure variables such as cultural sensitivity, communication efficacy, personalization, emotional involvement, and language accessibility, using a sample of 92 travelers from seven hotels in Erbil. The findings demonstrate the noteworthy favorable associations between these variables and the level of satisfaction experienced by tourists, underscoring the significance of cultural sensitivity, proficient communication, tailored encounters, and inclusiveness in influencing tourists' perspectives. In addition, the investigation of reliability serves to validate the internal consistency of the measurement scales employed, thus strengthening the credibility of the research outcomes. Suggestions for stakeholders in the hospitality industry encompass allocating resources towards cultural sensitivity training, enhancing communication channels, tailoring guest experiences to individual preferences, and fostering genuine cultural exchanges.